Do more specific plans help you lose weight? Examining the relationship between plan specificity, weight loss goals, and plan content in the context of a weight management programme. Issue 4 (6th October 2016) - Dombrowski, Stephan U.; Endevelt, Ronit; Steinberg, David M.; Benyamini, Yael
Abstract : Objectives: The conditions under which planning for behaviour change is most effective are not fully understood. In the context of a weight management programme, we examined the interrelationship between plan specificity, type of behaviour planned (diet vs. exercise), and weight loss goals. Design: Prospective design and content analysis of plans formed by participants of a 10‐week weight management programme. Methods: Participants ( n = 239) formulated two plans, for dietary and exercise behaviours, respectively. Plans were rated for specificity by examining the number of plan components. Weight loss goals were assessed by asking how much weight participants intend to lose. Weight was measured objectively each of the 10 weeks. Changes in body mass index (BMI) over time and the interactions between plan specificity and weight loss goals, for all plans and separately for diet and exercise, were estimated using linear mixed models. Results: Plan specificity was unrelated to weight loss, but interacted with weight loss goals in predicting linear change in BMI ( t = −2.48): More specific plans were associated with higher decreases in weight in participants with high weight loss goals. Separate interaction tests for plans formulated for diet and exercise change showed that more specific dietary plans, but not exercise plans, were associated with higher decreases in weight in participants with high weight loss goals ( t = −2.21). Conclusions: Within a population that is highly motivated to lose weight, the combination of high weight loss goals and formulating detailed plans for changing dietary behaviours may be most effective in supporting weight loss. Statement of contribution What is already known on this subject? More specific plans are associated with increased performance of health‐related behaviours. More motivated individuals form more specific plans. The interrelationship between plan specificity, plan content and behaviour‐related goals in relation intervention effectiveness has not been explored to date. What does this study add? The effectiveness of forming specific plans may depend on the strength of behaviour‐related goals as well as the behaviour selected for change. More detailed plans, in particular dietary plans, were related to greater weight loss, but only for participants with higher initial weight loss goals. Detailed exercise plans were not associated with weight loss, regardless of initial weight loss goals.